Maximizing Learning Outcomes by Socratic Questioning Exploring the Pedagogical Applications and Challenges among Language Lecturers at Universiti Malaysia Kelantan - Hum Chan; Iwan Zahar (2012)
Abstract: This study aims to explore the perception of language lecturers toward the pedagogical applications and challenges of Socrates Questioning for language teaching. Quantitative method with questionnaire was applied to collect data from 20 language lecturers at Universiti Malaysia Kelantan (UMK). Data was analyzed by SPSS. The findings revealed that applying Socrates questioning in language teaching can enhance teaching effectiveness, affect students’ learning behaviour and promote students’ learning activities that can produce optimal learning outcomes. However, fruitful learning outcomes depended on lecturers’ ability and skills to apply questions in pedagogical manner linking Socrates questions and questioning techniques regarding the target language, teaching procedures and learning activities that can enrich profound outcomes. Keywords: Learning Outcomes, Pedagogical Application, Socrates Questions